Introduction of inorganic nano-particles into a polymer matrix to restrain the initiation and propagation of electrical trees in the corona condition. Issue 84 (21st November 2017) - Shang, Chunyu; Du, Yanqiu; Kang, Hui
Abstract : In the corona condition, the initiation and propagation of electrical trees in a polymer matrix originates from the field enhancement effect. Abstract : In the corona condition, the initiation and propagation of electrical trees in a polymer matrix originates from the field enhancement effect. Driven by the alternating background electric field in the corona process, an alternating current would pass though the decomposition channel of the electrical tree, stimulating an enhanced local electric field on the tip of the electrical tree. When inorganic nano-particles with high corona-resistibility were introduced into the polymer matrix, in the corona process, the inorganic nano-particles were aggregatively deposited in the decomposition channels of the electrical trees and on the surface of the composite material. The decomposition channels were blocked and the alternating current was shut off, eliminating the enhanced local electric field on the tip of the electrical tree. As a result, the initiation and propagation of electrical trees were restrained and improved corona-resistibility was achieved for the polymer/nano-particles composite material.